Manajemen Stres Dengan Cara Berpikir Positif Di Masa Pandemi Covid-19 - Dyah Rachman Kuswartanti (Jurnal Bhakti Karya dan Inovatif, 2022)
The COVID-19 pandemic is very disturbing to the public and students who are required to do online learning when the current facilities are not too adequate. There are quite a number of obstacles when carrying out online learning systems such as unstable signals, quotas and pulses that run out quickly, online boredom/saturation and the number of tasks given when compared to laryngeal learning. The situation of the COVID-19 pandemic, makes most individuals need to carry out an adaptation process to meet the demands of the needs of the surrounding environment due to changes that occur in every aspect. The change in demands that switch to an online system also causes students and the general public to experience depressed conditions or what is usually referred to as stress. The purpose of holding this Community Service (PkM) is so that the community and students are able to manage stress by positive thinking in dealing with unexpected situations such as during the COVID-19 pandemic. This PkM is carried out using the Web Seminar (Webinar) method, using lectures and questions and answers for participants so that participants better understand and apply the content of the material presented by the presenters. The material presented in the Webinar includes recognizing problems and thoughts on yourself and how to take positive thinking steps to overcome the problems faced during the COVID-19 pandemic. The result of this PkM is that participants who take part in this activity are expected to be able to recognize mistakes in thinking and learn to manage their thoughts to be more positive and ready to face unexpected situations.